THE IMPLEMENTATION THEORY OF ISNAD CUM MATN HARALD MOTZKI : A HADITH STUDY ON ADMIRING ARABS - Haidar Masyhur Fadhil; Rizkiyatul Imtyas (Ushuluna: Jurnal Ilmu Ushuluddin, 2023)
This article aims to put Harald Motzki's isnad-cum-matn analysis theory to the test by looking at a hadith about loving Arabs amid some Muslim Arab cults. The theory used in this hadith study is based on the historical-critical approach (HCA), frequently used by Western scholars to investigate the authenticity of hadith. Harald Motzki's dating method involves simultaneously analyzing the transmission of hadith using the isnād and matan analysis methods. The primary guideline in tracing the hadith's origin is to analyze the transmission lines (isnad) by compiling and comparing variations of the hadith text with each other, determining the common link (cl) and partial common link (pcl) in the various transmission lines, and comparing the variants of the hadith text to determine whether the common link can be called the hadith's first transmitter. In the theoretical reflection on the hadith about loving Arabs, the author discovers that a second-century person named Abu Musallam is the common link and the author of the hadith with five people as partial common links, namely Al-Uqaili, Ali b. Hamsyaz, At-Tabrani, Habib b. Hasan, Faruq Al-Khatabi, and Hasan b. Yahya.